Interação sexual: perspectiva etológica do dimorfismo sexual humano - Silva, Araguari Chalar da (1979)
Sexual intercorirse, in a sense of a 'Mutual Action' demands the existence of partners dimorphically characterized since the chromossomial structure X-X or X-Y. Sexual differentiation, however, doesn't depend only on the chromossomial condition and can even be inverted when the hormonal action is changed. The available data show the androgen as one of the main agents of this differentiation, working on the 'basic' female organism in a masculinizing way. As long as we advance in the animal scale, the strict biological aspects loose in importance as the environemental conditions superimpose. In higher primates, if the proper conditions of learning are not found, sexual development fail to complete and copulation becomes impossible. In human beings, beyond this learning needs, socio-cultural factors answer for the considered masculine or feminine behavior that will be by each partner in interaction. The 'aesthetic notions' are also serioysly determined by cultural tradition with each people tending to consider their own racial traits as a sign of beauty. On a physical standpoint, however, we can try to stablish some constants, as the round shaped form for women and the athletic body built for men. Sett led the attraction and found the place and opportunity, sexual interaction will grow to a progressive genitalization that in the judeo-christian tradition societies will reflect in a probable sequence, from general petting kisses, breast and genital caressing until the genito-genital union. The meaning and the style in which each culture develops the physical contacts of sexual interaction may present a so great variety that this diversity has already been pointed as a typical human asquisition. So, contrary to the way pointed by the ideal of abstinence, is that capacity of searching and mantaining the pleasure beyond the simple sexual-organic activity, that, in sex, free the human being from animal limitations.